Metabolic requirements associated with GSH synthesis during in vitro maturation of cattle oocytes - Furnus, Cecilia Cristina (2008)
Glutathione (GSH) concentration increases in bovine oocytes during in vitro maturation (IVM). The constitutive amino acids involved in GSH synthesis are glycine (Gly), glutamate (Glu) and cysteine (Cys). The present study was conducted to investigate the effect of the availability of glucose, Cys, Gly and Glu on GSH synthesis during IVM. The effect of the amino acid serine (Ser) on intracellular reduced/oxidized glutathione (GSH/GSSG) content in both oocytes and cumulus cells was also studied. Cumulus-oocyte complexes (COC) of cattle obtained from ovaries collected from an abattoir were matured in synthetic oviduct fluid (SOF) medium containing 8 mg/ml bovine serum albumin-fatty acid-free (BSA-FAF), 10 μg/ml LH, 1 μg/ml porcine FSH (pFSH) and 1 μg/ml 17 beta-estradiol (17β-E2). GSH/GSSG content was measured using a double-beam spectrophotometer. The COC were cultured in SOF supplemented with 1.5 mM or 5.6 mM glucose (Exp. 1); with or without Cys + Glu + Gly (Exp. 2); with the omission of one constitutive GSH amino acid (Exp. 3); with 0.6 mM Cys or Cys + Ser (Exp. 4). The developmental capacity of oocytes matured in IVM medium supplemented with Cys and the cell number per blastocyst were determined (Exp. 5). The results reported here indicate (1) no differences in the intracellular GSH/GSSG content at any glucose concentrations. Also, cumulus cell number per COC did not differ either before or after IVM (Exp. 1). (2) Glutathione content in oocytes matured in SOF alone were significantly different from oocytes incubated with SOF supplemented with Cys + Glu + Gly (Exp. 2). (3) Addition of Cys to maturation medium, either with or without Gly and Glu supplementation resulted in an increase of GSH/GSSG content. However, when Cys was omitted from the IVM medium intracellular GSH in oocytes or cumulus cells was less but not significantly altered compared to SOF alone (Exp. 3). (4) Glutathione content in both oocytes and cumulus cells was significantly reduced by incubation with 5 mM Ser (Exp.4). (5) There was a significant increase in cleavage and blastocyst rates when Cys was added to maturation medium. In contrast, the cleavage, morula and blastocyst rates were significantly different when 5 mM Ser was added to maturation media. There was also a significant difference in mean cell number per blastocyst, obtained from oocytes matured with 5 mM Ser (Exp. 5). This study provides evidence that optimal embryo development in vitro is partially dependent on the presence of precursor amino acids for intracellular GSH production. Moreover, the availability of Cys might be a critical factor for GSH synthesis during IVM in cattle oocytes. Greater Ser concentration in IVM medium altered "normal" intracellular GSH in both oocytes and cumulus cells with negative consequences for subsequent developmental capacity.